Revision of the Nomenclature for the Bacillus thuringiensis Pesticidal Crystal Proteins - Crickmore, N. (American Society for Microbiology, 1998)
The crystal proteins of Bacillus thuringiensis have been extensively studied because of their pesticidal properties and their high natural levels of production. The increasingly rapid characterization of new crystal protein genes, triggered by an effort to discover proteins with new pesticidal properties, has resulted in a variety of sequences and activities that no longer fit the original nomenclature system proposed in 1989. Bacillus thuringiensis pesticidal crystal protein (Cry and Cyt) nomenclature was initially based on insecticidal activity for the primary ranking criterion. Many exceptions to this systematic arrangement have become apparent, however, making the nomenclature system inconsistent. Additionally, the original nomenclature, with four activity-based primary ranks for 13 genes, did not anticipate the current 73 holotype sequences that form many more than the original four subgroups. A new nomenclature, based on hierarchical clustering using amino acid sequence identity, is proposed. Roman numerals have been exchanged for Arabic numerals in the primary rank (e.g., Cry1Aa) to better accommodate the large number of expected new sequences. In this proposal, 133 crystal proteins comprising 24 primary ranks are systematically arranged.